SYMBOLIC COMPROMISES IN ELECTORAL ALLIANCES: A CASE STUDY OF THE 11TH PARLIAMENTARY ELECTION IN BANGLADESH - Rahman, Hafizur; Salehin, Md. Asfaq (Universitas Negeri Surabaya, 2025)
This study investigates the formation, objectives, and strategic dynamics of electoral alliances in Bangladesh’s 11th National Parliamentary Election (2018). Employing a qualitative case study approach, the research draws on 26 semi-structured interviews with candidates, party leaders, voters, academics, journalists, political analysts, and civil society representatives, alongside document analysis and media content review. The findings reveal that alliances were primarily driven by the pursuit of power, the consolidation of vote banks, and the enhancement of political legitimacy, often facilitated through the use of common electoral symbols. Notably, the Grand Alliance (Mohajote) emphasized the unification of pro-liberation forces, while opposition coalitions framed their collaboration as a broader movement for the restoration of democracy. Newly registered parties frequently contested under alliance symbols due to administrative constraints, prioritizing participation over independent identity. The study also identifies the role of personal interests in alliance politics, highlighting instances where individual gains shaped strategic decisions. These findings illuminate the complex interplay between ideology, strategy, and pragmatism in Bangladesh’s electoral politics, offering insights into the evolving nature of coalition-building and symbolic politics in democratic systems.